Efficiency and Legal Certainty in Civil Procedure: Registered Letter Summons After Supreme Court Circular No. 1 of 2023 - Muhammad Aziz Marzuki; Dian Latifiani; Ahmad Habiburrahman (Journal of Private and Commercial Law, 2025)
This article reassesses the legal effectiveness of registered letter summons as a mode of service of process in Indonesian civil procedure following the enactment of Supreme Court Circular No. 1 of 2023. The study addresses a central question: whether the use of registered mail enhances procedural efficiency without undermining due process guarantees in private law disputes. Employing a normative juridical method combined with a conceptual and statutory approach, this research analyzes relevant procedural rules, judicial interpretations, and emerging practices in civil litigation. The findings indicate that while registered letter summons offer measurable advantages in terms of cost reduction, administrative efficiency, and expedited proceedings, their implementation raises concerns regarding proof of proper service, defendant awareness, and the risk of default judgments rendered without genuine notice. These issues directly affect the principles of audi alteram partem, legal certainty, and fairness in private law adjudication. The novelty of this study lies in its focus on the transformation of service of process mechanisms within Indonesian civil procedure through the lens of digitalization and procedural reform, specifically examining the underexplored implications of Supreme Court Circular No. 1 of 2023. The article contributes to the development of private and commercial law scholarship by offering a critical framework for evaluating alternative service methods and proposing safeguards to balance efficiency with due process. It further provides practical recommendations for courts and policymakers to strengthen verification mechanisms and ensure the reliability of registered mail as a legally sound instrument of summons.